Private Network EDI vs. Internet Electronic Markets: A Direct Comparison of Fulfillment Performance - Yao, Yuliang; Dresner, Martin; Palmer, Jonathan (Management Science, 2009)
Prior literature has documented the performance benefits from the use of electronic data interchange (EDI) and the Internet. Using purchase and fulfillment records from the U.S. government's Federal Supply Service, we provide a direct comparison of performance between a private network EDI channel and an Internet electronic market. Performance is measured using order cycle time and complete orders fulfilled. Our findings show that the Internet-based electronic market outperforms the EDI-based channel on these two important measures. Order cycle times were significantly lower when using the Internet-based electronic market, whereas the percentage of complete shipments was significantly higher after controlling for product, transaction, seller, and buyer-specific factors. The electronic market even outperforms the EDI channel when buyer and transaction characteristics favor the use of EDI. Because EDI is still prevalent in many industries, these results point to the gains that may be realized by switching to the newer technology.